(3GdeLjO aj EYQGH GdbQBf GdeLjOs - (3CHh ESMGb EHQGgje Hf eMeO GdUaGbSj,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HMaX cJGHg hHYO adeG cGf GddSGf GdYQHi gh GdWQjb GdSfi Edi age eaQOGJ GdbQBf GdYRjR hJQcjHGJg hSejJg HGdeLjO ai EYQGH GdbQBf GdeLjO EYQGH GdHSedI s
(3BNQgG (B:s
(3ajdRe GdeMPhQ bdfG EPG bOQfGg HGdaYd hYHQfG Yfg HGdfaS ajRhd GdeMPhQ Ydi Cf GdCehQ GdebOQI s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B82s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1607s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJaSjQ hYdhe GdbQBfs